1971
DOI: 10.1149/1.2408167
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Lithium Oxide-Nickel Oxide System

Abstract: Thermodynamic activity measurements of dissolved lithium oxide in normalNiO‐Li2O solid solutions have been carried out within the homogeneity range to the solubility limit (about 33 a/o lithium). The measurements have been carried out by means of suitable galvanic cells, of the type normalPt/normalNiO‐Li2Ofalse(x2false)//normalintermediate electrolyte//normalNiO‐Li2Ofalse(x1false)/normalPt where α‐Li2SO4 and β‐spodumene have each been used as the intermediate electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

1971
1971
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…The degree to which this change is associated with the conversion to the #-spodumene crystalline structure as compared to changes in other materials properties, e.g., glass phase and/or relative amounts of glass and crystalline phases, is not known. For the #-spodumene phase, results published by Pizzini and co-workers (22,23) on polycrystalline sintered pressed pellets show a larger activation energy (,~ 1.16 eV) than that reported here, but a <To of about the same value. Thus the conductivity of the sintered polycrystalline #-spodumene samples they examined is even lower than that of our #-spodumene glass-ceramic samples.…”
Section: Materials Ionic Conductivity Studiescontrasting
confidence: 59%
See 1 more Smart Citation
“…The degree to which this change is associated with the conversion to the #-spodumene crystalline structure as compared to changes in other materials properties, e.g., glass phase and/or relative amounts of glass and crystalline phases, is not known. For the #-spodumene phase, results published by Pizzini and co-workers (22,23) on polycrystalline sintered pressed pellets show a larger activation energy (,~ 1.16 eV) than that reported here, but a <To of about the same value. Thus the conductivity of the sintered polycrystalline #-spodumene samples they examined is even lower than that of our #-spodumene glass-ceramic samples.…”
Section: Materials Ionic Conductivity Studiescontrasting
confidence: 59%
“…However, for solid electrolyte applications it is obviously important to enhance the ionic conductivity, and for this reason we have examined the ~-eucryptite materials. Some information on ionic conductivity is available on lithium aluminosilicates in the ~-spodumene phase (19,(22)(23)(24); however, there is very little information published on the ~-eucryptite materials (24), and none on the glass or glass-ceramic. Recent nuclear magnetic resonance (NMR) experiments (25) in conjunction with Raman scattering experiments (26) have shown that Li + motion does occur in LiA1SiO4 glass and glassceramic (~-eucryptite) materials.…”
mentioning
confidence: 99%
“…Previously, an instrument for the measurement of carbon monoxide in ambient air was described (1,2). The operating principle of that analyzer was based on the electrochemical oxidation of carbon monoxide (3) at a platinum-catalyzed Teflon-bonded diffusion electrode (4) ; the potential of this sensing electrode being maintained constant at a value where neither oxygen reduction nor electrolyte decomposition interfered with the measurement of the pollutant.…”
Section: Technicalmentioning
confidence: 99%
“…The conductivities of a number of lithium containing electrolytes have recently been reviewed by Pizzini (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation